Review on Central Administration under Akbar Rule: Analyzing the Central Administration and Unification Efforts under Akbar Rule (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In this Paper we will discuss about Akbar the Great (1556-1605) was a well-known Mughal (or Mughal) ruler and regarded as a great ruler due to his achievements in the military, politics, development and administration. In fact, he was regarded as the definitive founder of the Mughal Empire after his victory over an army led by Hemuin the Second Battle of Panipat in 1556. The victory has opened a way for Akbar to become the sole emperor in the Indian sub-continent and continued to wage wars against Hindu rajahs. To unify the vast Indian states under a single Mughal empire, Akbar introduced several administrative policies. The objective of this study is to analyze the Indian unification efforts under the Mughal Empire.